He gave us stories : the Bible student's guide to interpreting Old Testament narratives - Pratt, Richard L., 1953- (Phillipsburg, NJ : Presbyterian and Reformed, 1990)
Includes bibliographical references and index.
Keywords: Bible. -- study and teaching